Green product development and performance of Brazilian firms: measuring the role of human and technical aspects. (15th January 2015) - Jabbour, Charbel Jose Chiappetta; Jugend, Daniel; Jabbour, Ana Beatriz Lopes de Sousa; Gunasekaran, Angappa; Latan, Hengky
Abstract: The goal of this study is to present and test a conceptual framework that describes the technical aspects (TA), human/organizational aspects (HOA) of the adoption of green product development (GPD) practices and the effect of these practices on firms' environmental (EP), operational (OP) and market performance (MP). To this end, after reviewing the literature on these themes, a conceptual framework with 5 hypotheses is proposed. These hypotheses were tested on 62 Brazilian companies through structural equation modeling using SmartPLS 2.0M3. The main results of this study are as follows: (a) in general, the proposed framework obtained adequate goodness of fit statistics (GoF); (b) technological factors are shown to have an influence on the adoption of GPD practices, and those practices are related to company EP, OP and MP, thus confirming 4 hypotheses of the study; and (c) one of the study's hypotheses is not validated, indicating that the relationship of human/organizational aspects to GPD must be further analyzed. This work extends the literature because: (a) the conceptual framework tested in this study establishes several concepts that have been only partially tested in the previous literature; (b) this work presents evidence about Brazil, where the themes addressed herein have not been yet been thoroughly investigated; and (c) the non-validation of the hypothesis regarding the relationship between human/organizational aspects with respect to the adoption of product-related environmental practices requires attention. Highlights: Relationships between green product development and firms' performance are explored. Results from a survey conducted with Brazilian companies are presented. We confirm that green product practices influence firms' performance. We confirm that green product is influenced by technical aspects. The link between human aspects and green products deserves more research.